A tandem highly steroselective FeCl3-promoted synthesis of a bisindoline: synthetic utility of radical cations in heterocyclic construction - Ibrahim Ali , Noorbatcha (Elsevier BV, 2004)
A conceptually distinctive stereoselective construction of the novel dimer, N-[N'-acetyl-7,7'-bis-(3,4-dimethoxy-phenyl)-7,8,7',8'-tetrahydro-N'H-[8,8']biindolyl-N-yl]-ethanone 25 (bisindoline) is described below. These structures, which include 7-(3,4-dimethoxyphenyl)-indoline 24 (veratryl indoline), were obtained by the tactical combination of palladium-catalysed coupling which produced 10-acetamido-3,4-dimethoxystilbene 9, followed by FeCl3 induced oxidative cyclization/dimerization. All new structures were fully characterized by 1- and 2D NMR spectroscopy, (proton, carbon-13, COSY, HMBC, HMQC) and mass spectrometry. Configurational assignments were further supported by semi-empirical AMI calculations. Mechanistic interpretations, consistent with our results, are discussed.